Addition of Organic Acids to Base Wines: Impacts on the Technological Characteristics and the Foam Quality of Sparkling Wines - Paola Domizio; Alessandra Luciano; Antigone Marino; Luigi Picariello; Martino Forino; Francesco Errichiello; Giuseppe Blaiotta; Luigi Moio; Angelita Gambuti (Molecules, 2023)
Climate change is causing a significant decrease in the total acidity of grapes and related wines. This represents a serious issue for sparkling wine production. Consequently, before the second fermentation, the acidification of base wines is often necessary. However, the impacts of the most important organic acids on the foam properties of sparkling wines are not yet well known. The impacts of the addition of tartaric, malic, citric, and lactic acid on the quality of Falanghina and Bombino sparkling wines were evaluated. Analyses were performed soon after the second fermentation and one year after aging sur lees. The addition of each different organic acid to the two base wines resulted in significant changes in the sparkling wines not only in terms of pH, titratable acidity, and buffering capacity but also in the content of total amino acids and, in some cases, in the height of the foam and its stability over time. For both grape varieties, acidified wines showed a lower content of total amino acids in comparison with the control wines. The addition of lactic acid determined a higher persistency of the foam even after one year of aging sur lees only in Falanghina wines. The results obtained herein highlight the importance of organic acids and the pH of the base wines for the content of amino acids in sparkling wines. No strict correlation between organic acid addition and the foamability of wines was observed.